교통카드 자료를 이용한 서울시 지역별 대중교통 수단 선택 공간상관성 분석 - 박만식; Man Sik Park; 엄진기; Jin Ki Eom; 허태영; Tae Young Heo (Ŭngyong tʻonggye yŏnʼgu, 2013)
본 연구에서는 교통 분석존(서울시 행정동) 단위별로 대중교통 수단(버스, 도시철도)선택에 있어서 공간 상관성이 존재하는지 여부를 대중교통카드 자료를 기반으로 제시한다. 분석결과 버스를 탑승한 비율이 높은 지역들이 서로 이웃하여 그룹을 형성하고 있으며, 이들 지역은 도시철도 역사의 수가 버스 정류장에 비해 매우 적기 때문인 것으로 분석되었다. 버스에 탑승한 비율이 비슷한 그룹 간에는 공간 상관성이 존재하는 것으로 통계분석결과 나타났으며, 이러한 공간상관성은 향후 대중교통 수단선택 모형 구축에 고려할 수 있을 것으로 판단된다. 대중교퉁 수단선택에 있어 공간상관성의 존재는 대중교통 운영기관이 향후 대중교통카드를 기반으로 대중교통 노선계획, 운영계획을 수립함에 있어 중요한 정보가 될 것으로 기대된다. In this study, we provide empirical evidence of whether a spatial correlation among mode choices at the TAZ(Traffic Analysis Zone) level exists based on transit smart card data observed in Seoul, Korea. The results show that the areas with a higher probability that passengers choose to take a bus are clustered and that those regions have fewer metro stations than bus stations. We also found that the spatial correlation turned out to be statistically meaningful and provided an opportunity for the potential use of the spatial correlation in modeling mode choices. A reliable spatial interaction would constitute valuable information for transportation agencies in terms of their route planning and scheduling based on the transit smart card data.